2001
DOI: 10.1182/blood.v97.12.3875
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic hybridization analysis in adult T-cell leukemia/lymphoma: correlation with clinical course

Abstract: Sixty-four patients with adult T-cell leukemia/lymphoma (ATL; 18 patients with indolent subtype and 46 with aggressive subtype) associated with human T-lymphotropic virus type 1 (HTLV-1) were analyzed using comparative genomic hybridization (CGH). The most frequent observations were gains at chromosomes 14q, 7q, and 3p and losses at chromosomes 6q and 13q. Chromosome imbalances, losses, and gains were more frequently observed in aggressive ATL than in indolent ATL, with significant differences between the 2 AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
75
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(81 citation statements)
references
References 35 publications
4
75
1
1
Order By: Relevance
“…ATLL occurs in 3-5% of HTLV-1 carriers following a long latency period, which can range from 40 to 60 years (Yasunaga and Matsuoka, 2003). ATLL cells are derived from the malignant clonal expansion of an HTLV-1-infected CD4 þ T lymphocyte that has accumulated genetic lesions, including the activation of oncogenes or inactivation of tumorsuppressor genes (Tsukasaki et al, 2001). A previous study from our laboratory discovered these genetic lesions by spectral karyotyping with a high-density single-nucleotide polymorphism array and comparative genomic hybridization in ATLL; we found that the T-cell transcription factor (TCF8)/zinc-finger E-box binding homeobox 1 (ZEB1) was a candidate tumor suppressor in ATLL (Hidaka et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…ATLL occurs in 3-5% of HTLV-1 carriers following a long latency period, which can range from 40 to 60 years (Yasunaga and Matsuoka, 2003). ATLL cells are derived from the malignant clonal expansion of an HTLV-1-infected CD4 þ T lymphocyte that has accumulated genetic lesions, including the activation of oncogenes or inactivation of tumorsuppressor genes (Tsukasaki et al, 2001). A previous study from our laboratory discovered these genetic lesions by spectral karyotyping with a high-density single-nucleotide polymorphism array and comparative genomic hybridization in ATLL; we found that the T-cell transcription factor (TCF8)/zinc-finger E-box binding homeobox 1 (ZEB1) was a candidate tumor suppressor in ATLL (Hidaka et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Breakpoints in 14q11 and 14q32, as well as genomic amplifications of 14q32, are recurrent in ATLL. 44,45 However, not all cases with 14q11 breaks appear to involve TRCA/D. Moreover, the breaks in 14q32 in ATLL seem not to target TCL1.…”
Section: Discussionmentioning
confidence: 99%
“…The HTLV-1 viral Tax protein was shown to interact with human MAD1 (HsMAD1) protein and compromise its function by preventing homodimerization as well as heterodimerization with HsMAD2, thus leading to an inhibition of the M checkpoint (Campbell et al, 2001;Jin et al, 1998;Kasai et al, 2001;Neuveut and Jeang, 2002). ATL cells are karyotypically abnormal and are frequently present as pleiomorphic multinucleated giant cells (Itoyama et al, 2001;Kamada et al, 1992;Sadamori, 1991;Sadamori et al, 1991;Tsukasaki et al, 2001;Yoshida, 2001); the TaxHsMAD1 interaction and the IRF-4 mediated downregulation of cyclin B1 and EB1 thus provide a molecular explanation for the HTLV-I-induced karyotypic abnormalities in ATL cells (Figure 7).…”
Section: Discussionmentioning
confidence: 99%